2017
DOI: 10.5530/pj.2018.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Activities of Fractions from Dioscorea bulbifera L. Chloroform and Methanol Extracts on T47D Breast Cancer Cells

Abstract: Objective: To elucidate cytotoxic activity of fractions from chloroform and methanol extracts of D. bulbifera organs on T47D breast cancer cells. Method: The vegetative organs of D. bulbifera were extracted gradually using chloroform and methanol. Cytotoxicity tested on T47D cells using MTT Assay. The most toxic extract was fractioned by vacuum liquid chromatography (VLC) followed by thin layer chromatography (TLC). The extract and fractions potential were tested on the Vero cells using the same method as canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
6
0
3
Order By: Relevance
“…High concentrations of the main compounds can be considered part of the plant's defense system (Hossain et al 2014). The plant extracts contain many metabolites and compounds, each of which is capable of acting synergistically or antagonistically, these compound components can have the maximum effect if they are in complex conditions along with other compound components (Virganita et al 2009;Nur and Nugroho 2018). The MIC in this fraction was 32 mg mL.…”
Section: Discussionmentioning
confidence: 98%
“…High concentrations of the main compounds can be considered part of the plant's defense system (Hossain et al 2014). The plant extracts contain many metabolites and compounds, each of which is capable of acting synergistically or antagonistically, these compound components can have the maximum effect if they are in complex conditions along with other compound components (Virganita et al 2009;Nur and Nugroho 2018). The MIC in this fraction was 32 mg mL.…”
Section: Discussionmentioning
confidence: 98%
“…It was reported by Nur and Nugroho [ 32 ] that D. bulbifera extracts demonstrated a cytotoxic effect on T47D cell lines. This research result indicated that the chloroform extract of the D. bulbifera leaves was stronger in inhibiting the growth of the cells than the methanol extract.…”
Section: Discussionmentioning
confidence: 99%
“…We examined the effect of dalbergin on T47D cells via-bility using four complementary tests. In this experiment, we assessed T47D cell growth (24,25). Many polyphenols can decrease colony counts in estrogen receptor-positive human breast cancer cell lines (27).…”
Section: Discussionmentioning
confidence: 99%